Original paperRegaining venous access for implantation of a new lead - Kuśmierski, Krzysztof; Syska, Paweł; Maciąg, Aleksander; Oręziak, Artur; Kuśmierczyk, Mariusz; Przybylski, Andrzej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Introduction : Venous occlusion is a relatively common complication of endocardial lead implantation. It may cause a critical problem when implantation of a new lead is needed. Traditional methods result in leaving abandoned leads. The optimal approach seems to be the extraction of the damaged or abandoned lead, regaining venous access and implantation of a new lead. Aim: To assess the efficacy and safety of new lead implantation by the method of lead extraction. Material and methods: All transvenous lead extraction procedures (203 patients) between 1 August 2008 and 15 October 2012 were assessed. The analysis included cases with leads implanted for at least 6 months prior to extraction. Results: Regaining venous access was the main indication for lead extraction in 5 patients (4.9%). The reason for new lead implantation was lead damage (n = 7) and system up-grade to cardiac resynchronization therapy (CRT) (n = 3). In total, 23 leads were extracted (9 defibrillation leads, 12 pacing leads and 2 left ventricular leads). The mean time from the implantation was 92.2 ±43.2 (48-152) months. In all cases Cook mechanical sheaths were applied. The use of the Evolution system was necessary to extract 3 leads. In all cases the new leads were successfully implanted as planned. No serious complications occurred. Conclusions : Diagnosis of venous occlusion should not be a contraindication for ipsilateral implantation of the new lead, because the techniques of transvenous lead extraction enable successful regaining of venous access.